Novel mutation in the CHST6 gene causes macular corneal dystrophy in a black South African family. Issue 1 (December 2016) - Carstens, Nadia; Williams, Susan; Goolam, Saadiah; Carmichael, Trevor; Cheung, Ming; Büchmann-Møller, Stine; Sultan, Marc; Staedtler, Frank; Zou, Chao; Swart, Peter; Rice, Dennis; Lacoste, Arnaud; et al.
Abstract Background Macular corneal dystrophy (MCD) is a rare autosomal recessive disorder that is characterized by progressive corneal opacity that starts in early childhood and ultimately progresses to blindness in early adulthood. The aim of this study was to identify the cause of MCD in a black South African family with two affected sisters. Methods A multigenerational South African Sotho-speaking family with type I MCD was studied using whole exome sequencing. Variant filtering to identify the MCD-causal mutation included the disease inheritance pattern, variant minor allele frequency and potential functional impact. Results Ophthalmologic evaluation of the cases revealed a typical MCD phenotype and none of the other family members were affected. An average of 127 713 variants per individual was identified following exome sequencing and approximately 1.2 % were not present in any of the investigated public databases. Variant filtering identified a homozygous E71Q mutation inCHST6, a known MCD-causing gene encoding corneal N-acetyl glucosamine-6-O-sulfotransferase. This E71Q mutation results in a non-conservative amino acid change in a highly conserved functional domain of the humanCHST6 that is essential for enzyme activity. Conclusion We identified a novel E71Q mutation inCHST6 as the MCD-causal mutation in a black South African family with type I MCD. This is the first description of MCD in a black Sub-Saharan African family and therefore contributes valuable insights into the genetic aetiology of this disease, while improving genetic counselling for this and potentially other MCD families.